Moral character of Muslim personality: scale validation - Al-Ammar, Fawziah; Ahmed Mohamed, Ismaiel Hassanein; Nordin, Mohamad Sahari (www.iiste.org, 2012)
Psychological personality theorists had something to say about morality, but the topic of Islamic morality remains largely unstudied. This study investigates the indicators of the Moral Character of Muslim Personality (MCMP) as given in the context of Qur’anic verses. The results of Confirmatory Factor Analyses on data collected from 312 Yemeni secondary school teachers confirm eight dimensionalities of MCMP. These constructs cooperation, striving with wealth and self, reconciliation, voluntary charity, truth, fulfilling promises,forgivingness, and steadfastness) were operated and tested. The eight character traits were found to be grouped under one rubric of MCMP. The findings of the study establish psychometrically sound instrument derived from Islamic theory. There are several implications from the study that call for further research.